1997
DOI: 10.1016/s1074-7613(00)80356-8
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor Type 1 (CR1, CD35) Is a Receptor for C1q

Abstract: Molecular definition of the cellular receptor for the collagen domain of C1q has been elusive. We now report that C1q binds specifically to human CR1 (CD35), the leukocyte C3b/C4b receptor, and the receptor on erythrocytes for opsonized immune complexes. Biotinylated or radioiodinated C1q (*C1q) bound specifically to transfected K562 cells expressing cell surface CR1 and to immobilized recombinant soluble CR1 (rsCR1). *C1q binding to rsCR1 was completely inhibited by unlabeled C1q and the collagen domain of C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
157
2
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(167 citation statements)
references
References 66 publications
(14 reference statements)
5
157
2
3
Order By: Relevance
“…CR1 (CD35) binds mainly C3b, C4b and C1q [20,21], whereas CR2 (CD21) binds the natural proteolytic fragments iC3b, C3dg and C3d [22,23]. Flow cytometry with mAb to CR1 and CR2 confirmed that B cells are positive for CR1 and CR2 (data not shown).…”
Section: Microparticles Are Transferred To Pbmc and Endothelial Cellsmentioning
confidence: 88%
“…CR1 (CD35) binds mainly C3b, C4b and C1q [20,21], whereas CR2 (CD21) binds the natural proteolytic fragments iC3b, C3dg and C3d [22,23]. Flow cytometry with mAb to CR1 and CR2 confirmed that B cells are positive for CR1 and CR2 (data not shown).…”
Section: Microparticles Are Transferred To Pbmc and Endothelial Cellsmentioning
confidence: 88%
“…The CR1 gene is located on chromosome 1 at the locus 1q32 in a genetic cluster of complement activation genes (de Cordoba and Rubinstein 1986). CR1 is a multifunctional protein, which is widely expressed on the extracellular membrane of, B lymphocytes, monocytes, macrophages, erythrocytes, eosinophils, some CD4-positive T cells, dendritic cells, Langerhan cells in the skin glomerular podocytes and microglia as well (Crehan et al 2013;Klickstein et al 1988Klickstein et al , 1997Korotzer et al 1995;Liu and Niu 2009). CR1 has two isoforms: CR1-F and CR1-S, where the F means the ''fast'' isoform with a smaller molecular weight while the S refers to ''slow'' isoform (Aiyaz et al 2012).…”
Section: Complement Receptormentioning
confidence: 99%
“…CR1 reportedly has high affinity for C3b and lower affinity for iC3b, and also binds C4b, C1q, and MBL (12)(13)(14). Likewise, murine CR1 has binding sites for both C3b and C4b (15,16).…”
mentioning
confidence: 99%